Modern preconditions for the use of PVC profile window systems in the restoration of architectural monuments. - OSIPOV, Alexander; BONDARENKO, Mykola (Ways to Improve Construction Efficiency, 2025)
The protection and preservation of architectural monuments, as significant elements of Ukraine’s cultural heritage, is a highly relevant task, especially in the context of the post-war recovery of the country. The state register of immovable monuments of Ukraine lists over 20,000 architectural heritage sites, highlighting the scale of the restoration problem. In this context, the restoration of window structures in architectural monuments constitutes an unreasonably high share of the total restoration volume, primarily due to their frequent destruction during military actions. These conditions raise questions about the justification for the possibility of using modern window systems and technologies that ensure highly productive restoration of window structures in the shortest possible time. The preconditions for the application of modern window systems and technologies include a nationwide and social need for large-scale reproduction of window structures in architectural monuments in the shortest time, high quality and energy efficiency of these systems, as well as the technological nature of the installation process, the technique of which ensures the preservation of the identity of load-bearing wall structures and architectural elements, as well as the decoration of facades and interiors. Experience in the restoration of architectural monuments in our country and abroad demonstrates positive examples of using modern window systems, including those made from PVC profiles. It has been established that due to the high degree of factory readiness and quality of PVC profile window structures, their technological efficiency, and energy effectiveness, the use of modern window systems can ensure the execution of the projected restoration program for architectural monuments with high technical and economic indicators. The introduction of PVC window structures necessitates the development of a system of organizational and technological solutions for their installation, which meet the requirements for the restoration of architectural monuments and possess high technical and economic indicators.